2021
DOI: 10.3390/biomedicines9091094
|View full text |Cite
|
Sign up to set email alerts
|

Increased YKL-40 but Not C-Reactive Protein Levels in Patients with Alzheimer’s Disease

Abstract: Neuroinflammation is a common feature in Alzheimer’s (AD) and Parkinson’s (PD) disease. In the last few decades, a testable hypothesis was proposed that protein-unfolding events might occur due to neuroinflammatory cascades involving alterations in the crosstalk between glial cells and neurons. Here, we tried to clarify the pattern of two of the most promising biomarkers of neuroinflammation in cerebrospinal fluid (CSF) in AD and PD. This study included cognitively unimpaired elderly patients, patients with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The significance of inflammatory markers such as CRP, which can readily be determined in peripheral blood, has also been investigated repeatedly, especially in AD, with partly contradictory results [ 26 , 35 , 36 ]. While several studies showed significantly higher CRP levels in patients with AD than in healthy controls, a study by Nilsson et al showed that patients with VD had significantly higher CRP levels than those with AD [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of inflammatory markers such as CRP, which can readily be determined in peripheral blood, has also been investigated repeatedly, especially in AD, with partly contradictory results [ 26 , 35 , 36 ]. While several studies showed significantly higher CRP levels in patients with AD than in healthy controls, a study by Nilsson et al showed that patients with VD had significantly higher CRP levels than those with AD [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other sirtuins, sirtuin 2 promotes neurodegeneration in experimental models [ 61 ] and some SIRT2 variants increase AD risk [ 62 ]. Chitinase-like 1 is a marker of reactive gliosis and the innate immune response which shows human counterpart (chitinase 3-like 1 or YKL-40) increases in the CSF of AD patients, although changes in postmortem AD brain are controversial [ 63 , 64 ]. Young female offspring also showed a general increase in protein levels of GFAP and EGR1 as compared to the male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Young female offspring also showed a general increase in protein levels of GFAP and EGR1 as compared to the male offspring. The reactive astrocyte marker GFAP is increased in AD brain and in AD mouse models [ 32 , 63 ]. GFAP and chitinase-like 1 are differentially related to AD but both may mediate brain atrophy and cognitive impairment [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early findings have revealed that Aβ can activate microglia and astrocytes, causing inflammatory responses such as IL-1β production and increased expression of cyclooxygenase and inducible nitric oxide synthase (iNOS) to kill neurons. 51 Recent in vivo studies of AD patients also indicated that Aβ pathology was closely associated with astrocyte activation biomarkers such as chitinase-3-like protein 1 (YKL-40) 52 and glial fibrillary acidic protein (GFAP), 53 indirectly supporting the association between Aβ and astrocyte activation during AD development. Of note, Aβ needs a pre-stimulated environment to show its maximal pro-inflammatory potential.…”
Section: Relationship Between β-Amyloid (Aβ) Pathological Hallmark An...mentioning
confidence: 95%